2008
DOI: 10.1111/j.1365-3059.2008.01881.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of potato common scab pathogens in soil by quantitative competitive PCR with fluorescent quenching‐based probes

Abstract: Common scab of potato tubers caused by pathogenic Streptomyces spp. is a cause of serious economic loss worldwide. For the rapid and accurate quantification of pathogenic Streptomyces spp. residing in soil, a new competitive real-time PCR method using fluorescent quenching-based probes (quantitative competitive quenching probe PCR: QCQP-PCR) was developed. The virulence gene of pathogenic Streptomyces spp., nec1 , was selected as the target for QCQP-PCR. A specific primer set to amplify the nec1 gene, and a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…They were identified as Streptomyces scabies. These results are in agreement with those noted by several researchers who reported that S. scabies was responsible for common scab of potato (Lambert and Loria, 1989;Goyer and Beaulieu, 1997;Bencheikh and Setti, 2007;Manome et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…They were identified as Streptomyces scabies. These results are in agreement with those noted by several researchers who reported that S. scabies was responsible for common scab of potato (Lambert and Loria, 1989;Goyer and Beaulieu, 1997;Bencheikh and Setti, 2007;Manome et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…In order to achieve the successful biological control of plant diseases, including potato common scab, it is also important to understand the ecology and epidemiology of pathogens through the specific detection and quantification of pathogenic Streptomyces on potato tissue and in soil under field conditions. A TaqMan real-time PCR assay using virulence gene nec1 ( 5 ), SYBR Green quantitative real-time PCR assay using the txtAB operon ( 33 ), and quantitative competitive quenching probe PCR assay using the nec1 gene ( 26 ) have been used for the accurate detection and quantification of pathogenic Streptomyces in the potato. Although a good correlation has been reported between the presence of nec1 and pathogenicity, some nonpathogenic nec1 -positive strains and numerous pathogenic nec1 -negative strains have been described ( 33 ).…”
mentioning
confidence: 99%
“…The atpD sequence data suggest that the most common streptomycin producer from isolation work, S. griseus DSM 40236 and its close relatives, is found at a low density in soil.However none of the cloned atpD genes matched or were related to S. griseus DSM 40236. The molecular detection limit for plant pathogenic streptomycetes, , in soil has been calculated to be 10 3 gene targets per gram of soil for the txtAB gene [38] , 1.5×10 3 for the nec1 gene [39] and 10 2 for the 16 S gene [40] , suggesting that S. griseus soil populations may be lower than these values even after enrichment with chitin and starch. Other studies also support this finding as TCDNA studies of 13 streptomycetes from soil crusts in the Colorado Plateau [41] , 156 streptomycetes from prairie soil in the Cedar Creek Natural History Area [42] , and an isolate study including 3204 isolates from Singapore rainforests [43] failed to detect S. griseus , while a TCDNA study of temperate forest soils from Italy found one S. griseus sequence among 22 streptomycetes [44] , indicating that S. griseus is uncommon in soil.…”
Section: Discussionmentioning
confidence: 99%